General sociolinguistics, social semiotics and semiotics of culture - ex pluribus unum? Forty years after Language as Social Semiotic. - Zolyan, Suren (Sign Systems Studies, 2019)
The birth of social semiotics is usually associated with the publication of Michael Halliday's book Language as Social Semiotic (1978). We try to draw attention to possible new developments in social semiotics, which still remain a potential transdisciplinary project for social sciences. In order to do this, we address the interrelation between sociolinguistics, social semiotics and the semiotics of culture. All of these describe mechanisms of meaning production and translation beyond linguistic structures. The differentiation between these workings is based on a distinc tion between various aspects of meaning production and communication and functional characteristics of goal setting. The complexity of these processes legitimates the complexity of methodology used to describe them. Interconnection between different domains and aspects may create synthetic methods based on the dynamic approach to meaning production and transmission.